Effectiveness of a self-prepared educational module on newborn and maternal self-care and its impact on maternal confidence, breastfeeding self-efficacy, and depression among postpartum primipara mothers in a selected hospital, Gujarat - Vaishnav, Smruti; Mol Raju, Princey (International Journal Of Community Medicine And Public Health, 2025)
Background: Newborns face the highest risk of mortality during the first 28 days of life, accounting for nearly half of all under-five deaths. Despite progress, many neonatal deaths are still linked to inadequate care during and immediately after birth. Strengthening maternal confidence and knowledge in newborn care is therefore critical. Methods: This quasi-experimental study was conducted among 200 primiparous postpartum mothers at a tertiary care hospital to assess the effectiveness of a self-prepared educational module on selected variables like maternal confidence, breastfeeding self-efficacy and post-natal depression. Participants were selected using convenient sampling and assessed using a self-structured questionnaire and standardized tools including the maternal confidence questionnaire, breastfeeding self-efficacy scale, and edinburgh postnatal depression scale. The intervention group received the educational module, and pre- and post-test data were analyzed using descriptive and inferential statistics. Results: The study showed a statistically significant improvement in maternal confidence (p=0.0014) among mothers who received the module, while no significant differences were observed in breastfeeding self-efficacy and postnatal depression. Conclusions: The study highlighted the importance of structured educational interventions in enhancing maternal confidence and promoting better postnatal outcomes, suggesting that such modules should be integrated into routine postnatal care programs.